Homeless people and their dogs: exploring the nature and implications of the Human-Companion Animal Bond (H-CAB) between homeless owners and their dogs - Scanlon, Louise (2020)
Homelessness in the UK is an issue of increasing concern as the national homeless population continues to rise. Many of those who find themselves in situations of homelessness are accompanied by pets, often dogs. Dog ownership has been shown to positively affect human physical, psychological and social health and it is likely these influences extend to homeless dog owners. Contrary to popular opinion, dogs belonging to homeless owners appear generally healthy. Unfortunately, few homeless services accommodate pet owners, and many dog owners would sooner remain in precarious living situations than part with their dogs. This study aims to explore the nature of the bond between homeless people and their dogs and assess its implications for the health and welfare of both parties. Twenty homeless dog owners were interviewed regarding their experiences of the bond they have with their dog. The health and welfare of twenty-one homeless-owned dogs was assessed using the PDSA Petwise MOT. Results suggest that the health and welfare of homeless-owned dogs is not compromised as is often assumed. It is often presumed that homeless-owned dogs may experience malnutrition, however the results of the current study found that homeless-owned dogs are more likely to be at risk of being overweight, an issue that is also frequently reported within the housed dog population. On the other hand, elements of welfare including companionship appeared to be better catered to than is recorded within the housed dog population. Results also found that dogs often exist as crucial support systems for their homeless owners, providing instrumental benefits to psychological and social health. In addition, desistance and engagement in pro-social behaviours as a result dog ownership and the associated responsibility was also identified. Re-evaluating existing stigma and reviewing current policies regarding homeless pet ownership are warranted in order to better support both homeless owners and the dogs that accompany them.